Performance optimization analysis of cleaning mechanism for bottom frozen sticky float coal in train body based on Edem-RecurDyn co-simulation - XIE Miao; Ll SiYao; LIU Yi; NIE RenDong; ZHANG HongYu; ZHU Yun; LIU DongXu (Jixie qiangdu)
As one of main equipments of coal transportation, the transportation efficiency of train skin has always been the focus of the coal transportation industry. Under the condition of low temperature in winter in northern China, the main reason affecting the transportation efficiency is that the water contained in coal is adhered to the inner surface of the uneven carriage, and gradually diffuses from the surface of the carriage to the inside of the coal, finally, the phenomenon of frozen car causes the equipment to be unable to continue to run. In this paper, firstly, based on the existing problems of different cleaning methods, combined with the actual project, an automatic frozen sticky floating coal cleaning mechanism was designed and its cleaning performance was optimized. Through theoretical research and analysis, the floating coal frozen particle model was established. Secondly, the movement of the disc cutter during the cleaning process was analyzed, and the mechanical model and mathematical model were established. Finally, the multi-body dynamics software RecurDyn was used to simulate the performance of the cleaning drum at the bottom of the cleaning mechanism. The influences of different drum speed, traction speed and cleaning depth on the cleaning performance was solved, and the performance parameter matching scheme with the smallest cleaning retance and the lowest energy consumption was sought by optimization. The results show that the cleaning efficiency of the cleaning mechanism is less affected by the drum speed. With the increase of the drum speed, the cleaning resistance fluctuates within a certain range. As the traction speed continues to increase, the cleaning resistance firstly decreases and then gradually increases; the cleaning depth has the greatest influence on the cleaning resistance. With the increase of the cleaning depth, the cleaning resistance increases continuously. According to the influence law of single factor parameters on the cleaning resistance, the response surface method V was used to simulate the comprehensive influence law in a reasonable range. After the objective function was obtained, the mathematical model was solved by Matlab to obtain the optimal solution. When the drum speed is 78 r/min, the traction speed is 0.05 m/s, and the cleaning depth is 100 mm, the cleaning mechanism has the lowest resistance and the lowest specific energy consumption of 0.22 kWh/m3, and the performance of the cleaning mechanism is optimal.